(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: Caesarean Section (CS) rates are rising globally, including in multigravid women who previously delivered vaginally. Prior vaginal delivery often gives a false sense of security, leading to inadequate antenatal care and delayed recognition of complications, increasing maternal and neonatal risk. Proper monitoring, early detection and timely management can improve outcomes and reduce unnecessary CS. The purpose of the study to assess the fetomaternal outcome among these patients and to find out the measures to be taken for safe prevention of the primary cesarean delivery. Materials and methods: A prospective observational study was conducted in the Department of Obstetrics & Gynaecology, Chittagong Medical College Hospital, from March 2023 to February 2024. A total of 89 multigravid women with previous vaginal delivery underwent elective or emergency CS. Data were collected using a structured proforma and analyzed descriptively. Results: Out of 201 multigravida deliveries, 89 (44.3%) were primary CS. Most patients were 18–25 years (40.4%) rural (53.9%) and housewives (88.8%). Common risk factors were postdated pregnancy (23.6%) and preeclampsia (19.1%). Main indications included fetal distress (20.2%) malpresentation (16.9%) and severe pre- eclampsia/eclampsia (15.7%). Emergency CS accounted for 80.9%. Maternal morbidity occurred in 22.5% (Mainly wound infection 12.4%) while neonatal morbidity was 60.7%, chiefly birth asphyxia (34.8%) meconium aspiration (10.1%) and sepsis (7.9%). Stillbirths and neonatal death were 6.7% and 3.4% respectively. Conclusion: Primary CS in multigravid women is common, mainly due to fetal distress and malpresentation and is associated with significant maternal and neonatal morbidity. Strengthening antenatal care and intrapartum monitoring could improve outcomes. JCMCTA 2025 ; 36 (2) : 25-30